2018
DOI: 10.1016/j.euroneuro.2018.08.005
|View full text |Cite
|
Sign up to set email alerts
|

Nicotine improves probabilistic reward learning in wildtype but not alpha7 nAChR null mutants, yet alpha7 nAChR agonists do not improve probabilistic learning

Abstract: Cognitive impairments, e.g., reward learning, are present in various psychiatric disorders and warrant treatment. Improving reward-related learning could synergistically enhance psychosocial treatments and cognition generally. A critical first step is to understand the mechanisms underlying reward learning. The dopamine system has been implicated in such learning, but less known is how indirect activation of this system may affect reward learning. We determined the role of alpha7 nicotinic acetylcholine recept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 69 publications
(84 reference statements)
0
5
0
Order By: Relevance
“…[1][2][3][4] Its mode of action involves interacting with various subtypes of acetylcholine receptors, thus modulating neurotransmitter release. 5,6 Consequently, nicotine has emerged as a promising therapeutic candidate for neurodegenerative disorders like Alzheimer's disease (AD) and Parkinson's disease (PD). Notably, a7 nicotinic acetylcholine receptors (a7 nAChRs) rank as the second most prevalent subtype of nicotinic acetylcholine receptors in the brain, regulating the release of multiple neurotransmitters, including g-aminobutyric acid, glutamic acid, and dopamine.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] Its mode of action involves interacting with various subtypes of acetylcholine receptors, thus modulating neurotransmitter release. 5,6 Consequently, nicotine has emerged as a promising therapeutic candidate for neurodegenerative disorders like Alzheimer's disease (AD) and Parkinson's disease (PD). Notably, a7 nicotinic acetylcholine receptors (a7 nAChRs) rank as the second most prevalent subtype of nicotinic acetylcholine receptors in the brain, regulating the release of multiple neurotransmitters, including g-aminobutyric acid, glutamic acid, and dopamine.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, even when the same task is used, different designs may result in different aspects of cognition being measured. For example, VD and VDR tasks in previous studies have largely been performed in “classic” operant chambers where the visual cue is a single cue light illuminated above the correct or incorrect lever (Cole et al, 2015; Ortega et al, 2013; Milienne-Petiot et al, 2018). Thus, mice/rats are required only to attend to a single cue and to learn to approach or avoid that cue.…”
Section: Discussionmentioning
confidence: 99%
“…In humans, a meta-analysis reported positive effects of nicotine or smoking on attention, as well as short-term episodic and working memory (Heishman et al, 2010), while several other studies have similarly demonstrated enhanced performance on tests of continuous attention, computational processing, and memory (DeVito et al, 2014; Myers et al, 2008; Warburton et al, 1992). In rodent studies, nicotine improved VD in rats and three mouse strains (F. Bovet-Nitti, 1966, 1969), and facilitated reversal learning in a probabilistic reversal learning tasks (Milienne-Petiot et al, 2018). However, conversely, nicotine has also been reported to impair reversal learning in VD tasks, suggesting that nicotine may not improve cognitive function indiscriminately (Cole et al, 2015; Ortega et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The PRLT is a rodent operant task used to measure reward and punishment learning contingencies as well as behavioral flexibility when these reward/punishment contingencies are switched (Amitai et al, 2014;Milienne-Petiot et al, 2018). In short, the animal must choose between two differentially rewarded options, one with a high probability of reward (80:20) and another with a low probability (20:80).…”
Section: Probabilistic Reversal Learning Task (Prlt)mentioning
confidence: 99%